PEREMPUAN DALAM MINORITAS PENDIDIKAN - Handoko Ja’far (Ta`Limuna: Jurnal Pendidikan Islam, 2015)
Maxim, al-um madrasatun that mother is precisely a female, who considered has an important role in educating her children confirms that education and female are like a coin, it can’t be separated each other. In a history of Islam, the involvement of prophet’s wives as an inspiration demonstrated the truth of their role. Unlike female education in the early Islam, in which education acquisition was the same portion for both male and female as it is justified in prophetic saying. Nowadays, come along with the end of Islamic golden age, the opportunity for female education is intentionally limited by the legality of fiqh and stereotype reason, genital. This article presents the contrast of female education in two different eras with its inequality chance and the trouble with.